2019
DOI: 10.1111/adb.12798
|View full text |Cite
|
Sign up to set email alerts
|

N‐Acetylcysteine treatment during acute stress prevents stress‐induced augmentation of addictive drug use and relapse

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…Other preclinical studies have also shown similar effects on anxiety-like behavior and proinflammatory cytokine expression within the brain using COX-2 inhibitors (Gamble-George et al, 2016;Lee et al, 2016), and human studies suggest that anti-inflammatory treatments such as COX-2 inhibitors may be effective in reducing depression symptoms (Köhler et al, 2014). Interestingly, the antioxidant N-acetylcysteine (NAC) was recently shown to inhibit conditioned stress-induced cocaine and alcohol seeking when administered during or immediately following restraint stress (Garcia-Keller et al, 2020), which raises the question as to whether suppression of oxidative stress and inflammation via NAC treatment is therapeutic in this context. Importantly, NAC is currently being investigated clinically for its use in treating comorbid AUDs and PTSD (Back et al, 2020).…”
Section: Posttraumatic Stress Disordermentioning
confidence: 95%
“…Other preclinical studies have also shown similar effects on anxiety-like behavior and proinflammatory cytokine expression within the brain using COX-2 inhibitors (Gamble-George et al, 2016;Lee et al, 2016), and human studies suggest that anti-inflammatory treatments such as COX-2 inhibitors may be effective in reducing depression symptoms (Köhler et al, 2014). Interestingly, the antioxidant N-acetylcysteine (NAC) was recently shown to inhibit conditioned stress-induced cocaine and alcohol seeking when administered during or immediately following restraint stress (Garcia-Keller et al, 2020), which raises the question as to whether suppression of oxidative stress and inflammation via NAC treatment is therapeutic in this context. Importantly, NAC is currently being investigated clinically for its use in treating comorbid AUDs and PTSD (Back et al, 2020).…”
Section: Posttraumatic Stress Disordermentioning
confidence: 95%
“…N-Acetylcysteine (NAC), a precursor of L-cysteine and the antioxidant glutathione (GSH), is found in plants, especially the onion [96][97][98]. NAC has been used as an adjuvant therapy in many psychiatric disorders (e.g., Alzheimer´s disease, schizophrenia, autism, addiction, substance abuse, obsessive-compulsive and mood disorders [24,[99][100][101][102][103][104]), with promising results and no relevant side effects after its administration against inflammation [97]. The use of NAC in a chronic unpredictable mild-stress animal model inhibited the levels of pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) in the hippocampus and prefrontal cortex and exhibited antidepressant-like effects [71].…”
Section: N-acetylcysteine Decreases Inflammatory Responsementioning
confidence: 99%
“…A recent preclinical study in an animal model of comorbid post-traumatic stress disorder and SUDs showed that NAC could be used prophylactically to prevent or reverse the vulnerability to undergo stressinduced escalation of alcohol use and conditioned stress-induced alcohol (57).…”
Section: Alcohol and N-acetylcysteinementioning
confidence: 99%